MODERNIZATION OF THE PRINCIPLES OF THE SECURITY SYSTEM OF BUSINESS ENTITIES - Поліщук, Інна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Goal: since the legal support of economic activity is understood as a process of legal regulation of relations of its subjects and the implementation of legal requirements aimed at providing the necessary conditions for their development, stability of economic activity, as well as organization and protection from various external and internal threats. an effective legal mechanism to ensure the security of economic activity. In the context of creating a unified system of business security, the article considers and summarizes various approaches to defining the principles of security of the subjects of such activities as the main starting points that create the legal and economic basis for their safe operation and development. The issue of a systematic approach to the effective management of business entities due to the need to develop a comprehensive modernized principles and their further implementation in modern legislation is studied. Research methods: methods of comparison, systematization, generalization, grouping and system approach of complexity of application of principles of ensuring safety of business entities were used. Results: the definition of the principles of ensuring the security of economic entities is specified and the need to modernize their system in accordance with modern conditions, threats and risks of economic activities is substantiated. Discussion: problems of finding modern means of protection and tools of legal regulation to ensure the security of economic entities.